Epilepsy mortality in Wales during COVID-19. Issue 9 (12th August 2022) - Daniels, Helen; Lacey, Arron S; Mikadze, David; Akbari, Ashley; Fonferko-Shadrach, Beata; Jolling-Hurst, Joe; Rees, Mark I; Powell, Robert H; Kerr, Michael P; Pickrell, William Owen
Abstract : Purpose: We aimed to compare mortality rates in people with epilepsy in Wales during the pandemic with pre-pandemic rates. Methods: We performed a retrospective study using population-scale anonymised health records. We identified deaths in people with epilepsy (DPWE), those with a diagnosis of epilepsy, and deaths associ- ated with epilepsy (DAE), where epilepsy was recorded as a cause of death. We compared death rates in 2020 with average rates in 2015–2019 using Poisson models. Results: There were 188 DAE and 628 DPWE in Wales in 2020 (death rates: 7.7/100, 000/year and 25.7/100, 000/year). The average rates for DAE and DPWE from 2015 to 2019 were 5.8/100, 000/year and 23.8/100, 000/year, respectively. Death rate ratios (2020 compared to 2015–2019) for DAE were 1.34 (95%CI 1.14–1.57, p<0.001) and for DPWE were 1.08 (0.99–1.17, p = 0.09). The death rate ratios for non-COVID deaths (deaths without COVID mentioned on death certificates) for DAE were 1.17 (0.99–1.39, p = 0.06) and for DPWE were 0.96 (0.87–1.05, p = 0.37). Conclusions: The significant increase in DAE in Wales during 2020 could be explained by the direct effect of COVID-19 infection. Non-COVID-19 deaths have not increased significantly but further work is needed to assess the longer-term impact.